Fabrication of robotic firefighting - Abdul Rahman, Muhammad Zulqarnain (2025)
Now days there are a lot of fire cases due several reason and because of that firefighters tend to had a lot more job in a more job that can cause their life due to the traditional firefighting methods. Such as, working in a large fire that can cause heat exhaustion upon the firefighters, thick smoke that can affect their visibility and unstable structure that can collapse anytime. So, the objective of this project is about developing a firefighting robot that can autonomously enter hazardous fire situation without risking any human life, the robot is tasked to detect fire source and efficiently distinguish fire while reducing risks to human responders. The robot consists a set of heat sensors for high temperature and control algorithm to move the robot and extinguish the fire source. It is anticipated that the development of firefighting robot will significantly enhance firefighting operations by improving response times, reducing human exposure to hazards, and increasing overall operational efficiency. The robot's autonomous capabilities and functionalities are expected to contribute to safer and more effective firefighting practices in challenging scenarios